Cockroach allergen serine proteinases: Isolation, sequencing and signalling via proteinase‐activated receptor‐2. Issue 7 (27th April 2017) - Polley, D. J.; Mihara, K.; Ramachandran, R.; Vliagoftis, H.; Renaux, B.; Saifeddine, M.; Daines, M. O.; Boitano, S.; Hollenberg, M. D.
Summary: Background: Allergy to the German cockroach ( Blattella germanica) is a significant asthma risk factor for inner‐city communities. Cockroach, like other allergens, contains trypsin‐like enzyme activity that contributes to allergenicity and airway inflammation by activating proteinase‐activated receptors (PARs). To date, the enzymes responsible for the proteolytic activity of German cockroach allergen have not been characterized. Objectives: We aimed to identify, isolate and characterize the trypsin‐like proteinases in German cockroach allergen extracts used for clinical skin tests. For each enzyme, we sought to determine (1) its substrate and inhibitor enzyme kinetics (Km and IC50), (2) its amino acid sequence and (3) its ability to activate calcium signalling and/or ERK1/2 phosphorylation via PAR2. Methods: Using a trypsin‐specific activity‐based probe, we detected three distinct enzymes that were isolated using ion‐exchange chromatography. Each enzyme was sequenced by mass spectometery (deconvoluted with an expressed sequence tag library), evaluated kinetically for its substrate/inhibitor profile and assessed for its ability to activate PAR2 signalling. Findings: Each of the three serine proteinase activity‐based probe‐labelled enzymes isolated was biochemically distinct, with different enzyme kinetic profiles and primary amino acid sequences. The three enzymes showed a 57%‐71% sequence identity with a proteinase previously cloned from the American cockroach (Per a 10). Each enzyme was found to activate both Ca ++ and MAPK signalling via PAR2. Conclusions and Relevance: We have identified three different serine proteinases from the German cockroach that may, via PAR2 activation, play different roles for allergen sensitization in vivo and may represent attractive therapeutic targets for asthma.